Micro-Financing Rural India: a Review of Self-help Group Banking in India. - Rahul Saha (2007)
The Self-Help Group movement in India is now two decades old. Over this time, the movement has had a considerable positive impact on the social, economic and political lives of the rural poor in the country. It has not only increased the level of prosperity in rural India by increasing access to credit but has also helped bring about cohesion within rural communities and has increased political participation of those who are marginalised within their communities. At the same time, however, it is recognised that if the movement is to achieve its ambitious aim of poverty eradication, there is still a long way to go and much that can be done. This paper carries out a historical analysis of the Self-Help Group movement in the country, and compares it with other available models of microfinance, in order to assess its success and failures and to suggest strategies which can strengthen it further.